Fenomenologi, logika, dan strategi pengembangan ilmu - fawaid, Wafi; Nabila, Nafa Khibrotun; Al-Amiroh, Nafisah; Al-Febriansyah, Dava Xavi (Maliki Interdisciplinary Journal, 2025)
The three basic elements of science development that philosophy of science most often focuses on are phenomenology, logic, and science development strategies. They play an important role in understanding how science is formed, verified, and applied in all areas of life. The purpose of this research is to find out the relationship between these three basic elements, namely phenomenology, logic, and science development strategies with the science that has developed. This research is a library research whose data sources are taken from books, journals, and articles, as well as the works of UIN Maulana Malik Ibrahim Malang lecturers written on the UIN Malang repository page which are related and relevant to the research conducted. The results of this study are phenomenology as a source of experience, logic as a rationalization tool, and science development strategies as a development path have a very close relationship in compiling integral and reflexive scientific thinking steps in carrying out science. The three are interrelated in the discussion of contemporary philosophy of science, and further understanding of the interconnectivity between the three can provide opportunities to build a more integral, inclusive and transformative paradigm of science.